Degradation and recovery of swards - Padilla, C?sar; Crespo, Gustavo; Sardi?as, Yurangel (Cuban Journal of Agricultural Science, 2009)
The degradation of swards is produced, in general, together with the loss of the natural fertility of the soils causing the decrease in cattle productivity and great economic losses. It is considered that a sward is degraded when desired species have lost their vigor and productive capacity per unit of area and per animal and unpopulated areas and undesired plants of poor yield and low nutritive value occupy the land surface. This provokes the ecological and economical deterioration, being incompatible with the productive cattle systems. Among the main causes of degradation of swards, there are the indiscriminate use of burning, the invasion of weeds, pests, and diseases, the climatic factors and the poor fertility of the soils. Among the most used techniques for the effective rehabilitation of degraded swards, there is the use of the subsolator, the subsolator doble plowing, plowing + harrowing, plowing + harrowing +organic matter, and plowing + harrowing + complete formula (0.5 t/ha). Out of them, those of the lowest cost-benefit ratio and technical- productive impact have been plowing + harrowing and plowing + harrowing + complete formula. In this study, some reasons were identified supporting the preference for conducting recovery techniques and renewal of degraded swards instead of carrying out new sowings in degraded swards. Key words: swards, renewal, recovery.